Hubungan Penggunaan Media Sosial Dan Pola Asuh Orang Tua Dengan Kesehatan Mental Remaja Di Smk N 03 Kota Bengkulu Tahun 2024 - Septiya, Septiya; Handayani , Tita Septi; Tranado , Hengki (Jurnal Multidisiplin, 2025)
According to data from the World Health Organisation (WHO), the number of people suffering from mental health disorders has increased to 450 adolescents, and currently the peak number of people suffering from mental health disorders worldwide has reached 1 billion people, with a prevalence of 20% among adolescents. Data from We Are Social and Houtsuite shows that social media users are estimated to reach 4.62 billion worldwide by January 2022. The purpose of this study is to investigate the relationship between social media use and parenting styles with adolescent mental health at SMK N 03 Kota Bengkulu in 2024. The method used was a quantitative research design employing an analytical cross-sectional study design. Data were collected by distributing questionnaires to 91 adolescent respondents at SMK N 03 Kota Bengkulu. The sampling technique used was proportional stratified random sampling. The results of the study revealed that nearly half of the respondents (44.0%) fell into the ‘frequent’ category for social media use, the majority of respondents (70.3%) had permissive parenting styles, and more than half of the respondents (59.3%) exhibited emotional mental disorders. Statistical tests revealed that social media use (0.012) and parenting style (0.146) were associated with mental health among adolescents at SMK N 03 Kota Bengkulu. There was a relationship between social media use and mental health among adolescents at SMK N 03 Kota Bengkulu in 2024, but no relationship between parenting style and mental health. Nearly half of the respondents (44.0%) use social media frequently.